The investigation of resting-state functional connectivity in male sprinters and endurance runners brains based on fNIRS - Mengqi Liu; Wenyan Zhao; Xiaocong Yan; Zhenghao Xue; Ying Qin (Scientific Reports)
Abstract Objective To investigate the impact of extended aerobic and anaerobic exercise on cerebral activity by analyzing the functional connectivity strength attributes of the cerebral cortex in endurance runners (aerobic) and sprint athletes (anaerobic) during the resting state with fNIRS. Method Thirteen sprinters and twelve endurance runners were assessed using a functional near-infrared spectroscopic imaging system to quantify resting-state functional connection strengths for HbO2, HbR, and HbT across the brain, namely in the prefrontal and primary motor cortex. Results (1) In the examination of functional connectivity of HbO2, the overall functional connection strength of the anaerobic group exceeded that of the aerobic group. In the regions of interest, the functional connection strength in the left and right prefrontal cortex of the anaerobic group surpassed that of the aerobic group. However, the functional connectivity strength in the right primary motor cortex of the aerobic group was greater than that of the anaerobic group. In comparisons between regions of interest, the functional connection strength between the left and right prefrontal cortex was greater in the anaerobic group. In contrast, the aerobic group had a more pronounced functional connectivity strength between the left and right primary motor cortex. (2) The functional connectivity study of HbR indicated that the mean whole-brain functional connection strength in the anaerobic group surpassed that of the aerobic group; however, no significant differences were seen between the two groups in intra- and inter-ROI comparisons. (3) The functional connectivity study of HbT indicated that the average brain-wide functional connection strength in the aerobic group surpassed that of the anaerobic group. In the regions of interest, the anaerobic group had greater functional connectivity strength in the right prefrontal cortex. In contrast, the aerobic group demonstrated more pronounced functional connectivity strength in the right primary motor cortex. The aerobic group exhibited greater functional connection strength between M1-R and M1-L throughout the regions of interest. Conclusion The aerobic group had enhanced functional brain connectivity in the primary motor cortex, whereas the anaerobic group demonstrated superior functional brain connectivity in the prefrontal lobe. Various exercise modalities will have distinct influences on neuroplasticity across different brain regions, establishing a novel theoretical framework for exercise training and clinical rehabilitation.